Design and Validation of a Novel Cable-Driven Hyper-Redundant Robot Based on Decoupled Joints. (2nd November 2021) - Huang, Long; Liu, Bei; Yin, Lairong; Zeng, Peng; Yang, Yuanhan
Abstract : In most of the prior designs of conventional cable-driven hyper-redundant robots, the multiple degree-of-freedom (DOF) bending motion usually has bending coupling effects. It means that the rotation output of each DOF is controlled by multiple pairs of cable inputs. The bending coupling effect will increase the complexity of the driving mechanism and the risk of slack in the driving cables. To address these problems, a novel 2-DOF decoupled joint is proposed by adjusting the axes distribution of the universal joints. Based on the decoupled joint, a 4-DOF hyper-redundant robot with two segments is developed. The kinematic model of the robot is established, and the workspace is analyzed. To simplify the driving mechanism, a kinematic fitting approach is presented for both proximal and distal segments and the mapping between the actuator space and the joint space is significantly simplified. It also leads to the simplification of the driving mechanism and the control system. Furthermore, the cable-driven hyper-redundant robot prototype with multiple decoupled joints is established. The experiments on the robot prototype verify the advantages of the design.